The Impact of COPD on Early Results After Cardiac Surgery - Atmani, Noureddine; Seghrouchni, Anis; Moutakiallah, Younes; Mounir, Reda; Abetti, Ayoub; Abdou, Abdessamad; Bamous, Mehdi; Nya, Fouad; Bellouize, Siham; Belkhadir, Mohamed; et al. (Cardiology and Cardiovascular Medicine, 2018)
Objective: Chronic obstructive pulmonary disease (COPD) is associated with significant morbidity and mortality after cardiopulmonary bypass (CPB). This study aimed to evaluate the impact of COPD on early post operative results. Patients and methods: Between January 1994 and December 2015, 2416 adult’s patients who underwent CPB are analyzed retrospectively. Among them 145 (6%) had a history of COPD. The relevant pre, intra and postoperative data were compared between COPD patients on non-COPD patients. Results: Patients with COPD are older than those without COPD (p<0.001). Coronary artery disease is more prevalent in COPD group. Patients with COPD were more symptomatic. Also, preoperative comorbidities such as peripheral arterial disease, renal dysfunction and left ventricular dysfunction were more prevalent in COPD group. No significant difference was noted between the two groups with regard to in-hospital mortality (p=0.17). But COPD correlated with many negative outcomes such as: prolonged mechanical ventilation, prolonged intensive care unit stay, excessive bleeding, pneumonia, low out post syndrome, postoperative renal failure and acute myocardial infarction. Conclusion: COPD did not increase in-hospital mortality after CPB, but it correlated with increased many postoperative complications.